125(3x-2)=25(2x+1)

Simple and best practice solution for 125(3x-2)=25(2x+1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 125(3x-2)=25(2x+1) equation:


Simplifying
125(3x + -2) = 25(2x + 1)

Reorder the terms:
125(-2 + 3x) = 25(2x + 1)
(-2 * 125 + 3x * 125) = 25(2x + 1)
(-250 + 375x) = 25(2x + 1)

Reorder the terms:
-250 + 375x = 25(1 + 2x)
-250 + 375x = (1 * 25 + 2x * 25)
-250 + 375x = (25 + 50x)

Solving
-250 + 375x = 25 + 50x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-50x' to each side of the equation.
-250 + 375x + -50x = 25 + 50x + -50x

Combine like terms: 375x + -50x = 325x
-250 + 325x = 25 + 50x + -50x

Combine like terms: 50x + -50x = 0
-250 + 325x = 25 + 0
-250 + 325x = 25

Add '250' to each side of the equation.
-250 + 250 + 325x = 25 + 250

Combine like terms: -250 + 250 = 0
0 + 325x = 25 + 250
325x = 25 + 250

Combine like terms: 25 + 250 = 275
325x = 275

Divide each side by '325'.
x = 0.8461538462

Simplifying
x = 0.8461538462

See similar equations:

| 4p-8=4(p-2) | | 04x+3.9=5.78 | | 2(x+4)=2(x-1)+3 | | 13-6x=-5(x-4) | | 4-4n=-4(n-1) | | 15+23=k+30 | | X+56.3=44.6 | | 14x+11+25+90=180 | | 3x+5(2x+y)=0 | | F(a)=10x-2 | | 8.1+x=3.6 | | 12(x-6)=-8-4 | | 37+2g=87 | | 4-n=4(n-1) | | 4(3x+1)=5x-6 | | -5(1-4m)=6m+37 | | 180=5x+12+6x-10 | | -7p+5p=-3p-31 | | 70-30=10+ | | 4x-12+5x=-30 | | 4x^3-4x^2-224x=0 | | 50-40=10+ | | -3v-3=-21 | | 30x+5(2x+y)=0 | | 7x=11+38 | | y=1.75x-1 | | 23-19=135 | | 12m+5=281 | | 7=-2-3n | | 22+8n=54 | | 20+7-4(x+1)= | | 2+7a+7=20+2a |

Equations solver categories